TRACING THE TREND ON DIGITAL COMPETENCE OF ENGLISH TEACHER; THE CHARACTERISTIC AND STRATEGIC IMPROVEMENT - Bahrani, Bahrani (Nurul Jadid University, 2023)
The current development has turned students into digital natives, also known as the digital generation, which demands that educators upgrade their competencies to align with the present conditions. This research aims to understand the characteristics and strategies for developing digital competencies among educators. The study adopts a qualitative approach with a case study design. Data collection is conducted through participant observation, in-depth interviews, and documentation. The collected data is analyzed using the Miles, Huberman, and Saldana data analysis techniques. The research findings reveal that the digital competency characteristics educators possess consist of digital literacy skills, the ability to interact and communicate through digital media, the ability to address the impact of digital content, and the ability to solve problems based on digital media. The strategies employed to enhance digital competencies include professional training and development, collaboration and knowledge exchange, monitoring and feedback, access to resources and instructional materials, technology-based projects and assignments, and support from school administrators.